Migrainous etiology of a unilateral nasal hemianopia visual field defect - Verrett, Jennifer Nicole; Vanderheyden, Kara (Canadian Journal of Optometry, 2023)
Patients who suffer from migraine headaches frequently visit an optometrist’s office for chief concerns of their headache or visual aura symptoms. Less well known is that migraine patients can experience transient loss of their visual field prior to or during a migraine attack. These visual field losses are measurable with optometric visual field testing, and have been reported to exist as numerous types of defects. An important component of visual field loss with a strictly migrainous etiology is the complete reversibility of the loss. A 53-year-old female patient presented to an optometrist’s office with acute migraine symptoms. Visual field testing revealed a unilateral nasal hemianopia. The patient was sent for an urgent CT scan to rule out intracranial pathology such as aneurysms, malignancies, or ischemic events. All imaging was negative, and visual field testing repeated after resolution of the migraine episode was essentially clear in both eyes. This case report introduces the current theories of the pathophysiology of migraine headache components, and explains why these are important for optometrists to understand. It also emphasizes the critical role that optometrists can take in the management of patients suffering from migraines.